Healthy Eating - Edited by Kistner, Stephanie (Millers Point Murdoch Books, 2003)
Following an introduction explaining the benefits of a healthy diet, this book contains photos of every recipe and includes clear step-by-step instructions to help the cook feel confident. A glossary illustrates some unusual ingredients.
Include Color Illustrations and Index
Keywords: Nutrition -- Cooking (Natural foods) -- Natural foods